Old and afraid of new communication technologies? Reconceptualising and contesting the 'age-based digital divide'. (June 2018) - Neves, Barbara Barbosa; Waycott, Jenny; Malta, Sue
Despite sociological attempts to critically address an age-based digital divide, older adults (65+) continue to be portrayed in the academic literature and public discourse as a homogeneous group characterised by technophobia, digital illiteracy, and technology non-use. Additionally, the role of socioeconomic factors and personal contexts in later life are often overlooked in studies on technology adoption and use. For example, older adults who are identified as least likely to use technology (frail, care-dependent, low socioeconomic/educational backgrounds) are typically described as a uniform cluster. Yet, research on digital technology use with this group remains scant – so what can we learn from studying technology adoption among them? This article discusses long-term deployment of new communication technologies with such a group of older adults, shedding light on the dynamics of technology adoption and contexts of use/non-use. It is based on a case study approach and a cross-cultural perspective, using Canadian and Australian mixed-methods research from two projects that included interviews, psychometric scales, and field observations. We present cases from these projects and contest the simplistic notion of an age-based digital divide, by drawing on Strong Structuration Theory to explore the interconnection of agency, structure, and context in the sociotechnical process of technology adoption and use/non-use among older adults.